Expert consensus on the bone repair strategy for osteoporotic fractures in China - Zhang, Hao; Hu, Yan; Chen, Xiao; Wang, Sicheng; Cao, Liehu; Dong, Shiwu; Shi, Zhongmin; Chen, Yanxi; Xiong, Liming; Zhang, Yunfei; Zhang, Dianying; Yu, Baoqing; et al. (Frontiers in Endocrinology, 2022)
Osteoporotic fractures, also known as fragility fractures are prevalent in the elderly and bring tremendous social burdens. Poor bone quality, weak repair capacity, instability and high failure rate of internal fixation are main characteristics of osteoporotic fractures. Proximal humerus, distal radius, tibia plateau, calcaneus and spine are popular osteoporotic fracture sites. Osteoporotic bone defects are common and need to be repaired by appropriate materials. Here the consensus from the Osteoporosis Group of Chinese Orthopaedic Association concentrates on the epidemiology, characters, management strategies of common osteoporotic fractures to standardize clinical practice in osteoporotic fractures.